A rare case of pneumobilia with pneumoperitoneum following paediatric blunt abdominal trauma - Mohan Marulaiah; B.M. Harsha; S. Swaroop (Elsevier, 2015)
Pneumobilia and pneumoperitoneum are two uncommon findings following blunt trauma abdomen. Existing literature identifies seven cases of traumatic Pneumobilia reported in adults, out of which only one had coexisting pneumoperitoneum. We report the first case of paediatric pneumobilia with coexisting pneumoperitoneum, following blunt abdominal trauma, which was managed conservatively.